Catalytic hydrothermal deoxygenation of sugarcane bagasse for energy dense bio-oil and aqueous fraction acidogenesis for biohydrogen production. (July 2023) - Kopperi, Harishankar; Venkata Mohan, S.
Graphical abstract: Highlights: Feasibility of Sugarcane bagasse (SCB) as potential feedstock for catalytic HTL. HTL derived biocrude can be served as alternative to fossil fuels. Ru/C resulted in higher bio-oil (28 %) and energy recovery (120.6 %) during HTL. The bioprocess (HTL-AF) showed 201 mL/g of bio-H2 with 64 % carbon conversion. The study supports zero-waste and carbon neutral efficient bio-refinery processes. Abstract: The study focuses on the effective conversion of sugarcane bagasse (SCB) by catalytic deoxygenation using various alkali and metal-based catalysts under N2 pressure employing water as solvent. The specific influence of catalyst over bio-crude yields (bio-oil and aqueous fraction) including energy recovery ratio was explored. The optimum catalytic condition (Ru/C) resulted in ∼ 70% of bio-crude and 28% of bio-oil with an improved HHV (31.6 MJ/kg) having 11.6% of aliphatic/aromatic hydrocarbons (C10 –C20 ) which can be further upgraded to drop-in fuels. The biocrude composed of 44% of aqueous soluble organic fraction (HTL-AF). Further, the carbon-rich HTL-AF was valorized through acidogenic fermentation to yield biohydrogen (Bio-H2 ). The maximum bio-H2 production of 201 mL/g of TOC conversion (K2 CO3 catalyst) was observed with 7.7 g/L of VFA. The SCB was valorized in a biorefinery design with the production of fuels and chemical intermediates in a circular chemistry approach.